2012
DOI: 10.1007/s00232-012-9511-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Transient Receptor Potential Vanilloid Channels TRPV5 and TRPV6 in Human Blood Lymphocytes and Jurkat Leukemia T Cells

Abstract: Regulation of Ca(2+) entry is a key process for lymphocyte activation, cytokine synthesis and proliferation. Several members of the transient receptor potential (TRP) channel family can contribute to changes in [Ca(2+)](in); however, the properties and expression levels of these channels in human lymphocytes continue to be elusive. Here, we established and compared the expression of the most Ca(2+)-selective members of the TRPs, Ca(2+) channels transient receptor potential vanilloid 5 and 6 (TRPV5 and TRPV6), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…In this work, we demonstrate that TRPV1, TRPV2, TRPV3 and TRPV4, all thermosensitive in nature, are endogenously expressed in Jurkat cells (human T cell line), primary T cells from human PBMCs and murine splenocytes. Our results are also in line with recent reports where it has been shown that functional TRPV5 and TRPV6 are expressed in T cells and that expression of these channels increases upon mitogenic activation. In this work, we show that TRPV1 and TRPV4 activation by specific ligands leads to Ca 2+ influx in purified murine T cells, indicating that these channels are present and functional even in resting T cells.…”
Section: Discussionsupporting
confidence: 93%
“…In this work, we demonstrate that TRPV1, TRPV2, TRPV3 and TRPV4, all thermosensitive in nature, are endogenously expressed in Jurkat cells (human T cell line), primary T cells from human PBMCs and murine splenocytes. Our results are also in line with recent reports where it has been shown that functional TRPV5 and TRPV6 are expressed in T cells and that expression of these channels increases upon mitogenic activation. In this work, we show that TRPV1 and TRPV4 activation by specific ligands leads to Ca 2+ influx in purified murine T cells, indicating that these channels are present and functional even in resting T cells.…”
Section: Discussionsupporting
confidence: 93%
“…Voltage‐current relations obtained from unitary currents recorded at different voltages displayed typical for calcium channels TRPV5/V6 inward rectification and a single channel conductance of 38 pS. The endogenous expression of TRPV5/V6 were confirmed by real‐time PCR and Western blot analysis [Vassilieva et al, ]. Here, we investigated the mechanisms of regulation of TRPV5/V6 channels in Jurkat T cells.…”
Section: Resultsmentioning
confidence: 98%
“…Earlier, in patch–clamp experiments on human blood lymphocytes (HBLs) and Jurkat T cell [Vassilieva et al, ], we showed the sensitivity of TRPV5/V6 channels in these cells to ruthenium red, a widely used, although not completely selective, inhibitor of TRPV5 and TRPV6 channels [Hoenderop et al, ; Schoeber et al, ]. In order to test if TRPV5/V6 channels mediate the Ca 2+ influx in these cells, ruthenium red was used in Ca 2+ measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The functional expression of the Ca 2+ -selective TRPV5 and TRPV6 channels was reported in mouse and human primary T cells and in Jurkat cells [15, 50, 51]. However, Trpv6 -/- mice have no reported immunological phenotype [52] and TCR-induced Ca 2+ influx in CD4 + T cells from Trpv6 -/- mice is normal [53].…”
Section: Trpv Channelsmentioning
confidence: 99%
“…However, the role of TRPV6 as a CRAC channel could not be established [54, 55] as BTP2 (a pyrazole derivative and CRAC channel inhibitor) did not affect the activity of the TRPV6 channel [56]. Recently, it was reported that both TRPV5 and TRPV6 are involved in Ca 2+ entry and cell cycle progression of human primary T cells and Jurkat cells [50]. The activity of these two channels in Jurkat cells was also shown to be modulated by extracellular pH [57].…”
Section: Trpv Channelsmentioning
confidence: 99%